Implementation Self Organizing Maps Method In Cluster Analysis Based on Achievement Suistainable Development Goal/SDG’s West Sumatera Province - AL Rezki Ivansyah; Fadhilah Fitri; Yenni Kurniawati; Tessy Octavia Mukhti (UNP Journal of Statistics and Data Science, 2023)
Indonesian government's commitment to implementing the Sustainable Development Goals (SDG’s) agenda, particularly in West Sumatra. The government of West Sumatra supports the objectives and targets of achieving SDG’s by optimizing the implementation of SDG indicators in the Rencana Aksi Daerah (RAD) for SDG’s of West Sumatra Province for the years 2022-2026. However, in its execution, there is a need for annual monitoring and evaluation of the RAD for SDG’s in West Sumatra Province. Clustering is employed to serve as a consideration for evaluating the implementation of RAD for SDG’s in West Sumatra Province for the years 2022-2026. The clustering method used is Self Organizing Map (SOM), an effective tool for visualizing high-dimensional data and can be used to map high-dimensional data into one, two, or three dimensions, representing connected units or neurons. The data used consist of 14 SDG indicator variables across 19 regencies/cities in West Sumatra in the year 2022, sourced from the official website and publications of the Badan Pusat Statistika (BPS) of West Sumatra Province. The analysis results in the formation of 3 clusters with different characteristics, which can be used as references in making policy decisions and effective strategies to enhance the implementation performance of SDG’s programs in West Sumatra Province.